Analysis of cutting forces and surface roughness in hard turning of AISI 4340 using multilayer coated carbide tool. (1st January 2014) - Basavarajappa, S.; Suresh, R.; Gaitonde, V.N.; Samuel, G.L.
The effects of cutting speed, feed rate and depth of cut on machinability aspects such as cutting force and surface roughness during hard turning of AISI 4340 steel using chemical vapour deposited (MT CVD) multilayer (TiN/MT-TiCN/Al2 O3 ) coated carbide tool were experimentally investigated. The experimental results revealed that the thrust force is more dominant than the cutting force and feed force. The thrust force increases with increased depth of cut and feed rate, while it decreases with increased cutting speed. The surface finish of the hardened component improved when the cutting speed has been elevated, whereas the surface quality deteriorated with increased feed rate. The worn parts of the cutting tool and machined surface were examined under scanning electron microscope (SEM). The flank and crater faces were severely grooved by the hard particles of work piece material exhibiting abrasive wear phenomenon. Intermittently, chipping on the tool rake face as well as catastrophic failure were also observed in continuous machining. Chip morphology study indicates the formation of saw toothed type serrated chips operating under several cutting conditions.